2012
DOI: 10.1128/jvi.05988-11
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of the Kaposi's Sarcoma-Associated Herpesvirus Nuclear Egress Complex and Formation of Nuclear Membrane Vesicles by Coexpression of ORF67 and ORF69 Gene Products

Abstract: The Kaposi's sarcoma-associated herpesvirus nuclear egress complex is composed of two proteins, ORF67 and ORF69. In this study, we have recapitulated the KSHV complex by coexpression of these two proteins in insect cells using expression from recombinant baculoviruses. The proteins form a complex at the nuclear membrane as judged by live-cell analysis of protein fusions tagged with green fluorescent protein (GFP) and mCherry. Ultrastructural analysis of infected cells showed that ORF67 expression results in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
81
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 26 publications
1
81
0
Order By: Relevance
“…The coexpression of these two proteins of PRV alone is sufficient to alter nuclear membranes, resulting in vesicle formation in transfected mammalian cells (13). Recently, we discovered, by using baculoviruses for gene expression, that the coexpression of the KSHV NEC proteins ORF67 and ORF69 could induce the same phenotype in insect cells (27). In our observations, we discovered that ORF67 is a potent inducer of host membrane proliferation.…”
mentioning
confidence: 52%
“…The coexpression of these two proteins of PRV alone is sufficient to alter nuclear membranes, resulting in vesicle formation in transfected mammalian cells (13). Recently, we discovered, by using baculoviruses for gene expression, that the coexpression of the KSHV NEC proteins ORF67 and ORF69 could induce the same phenotype in insect cells (27). In our observations, we discovered that ORF67 is a potent inducer of host membrane proliferation.…”
mentioning
confidence: 52%
“…Although lytic events and distortions of nuclear pores have been documented, the nuclear release of these viruses appears to predominantly occur by a budding mechanism (34,41,76). In support of the budding egress model, cooverexpression of nuclear egress proteins pUL31 and pUL34 results in the accumulation of vesicles between the inner and outer nuclear membranes, which may reflect an activity associated with budding during infection (21,32). …”
Section: Discussionmentioning
confidence: 88%
“…In the absence of either UL31 or UL34, viral replication is impaired and most capsids are retained in the nucleus (6, 7). The NEC is also sufficient to drive the formation of perinuclear vesicles in transfected cells (8,9), which demonstrated that UL31 and UL34 are the only viral proteins necessary for vesiculation. But these experiments left the function of the NEC in membrane budding unclear.…”
mentioning
confidence: 98%